2015
DOI: 10.17265/2159-5836/2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Aging With Disney and the Gendering of Evil

Abstract: and Frozen (2013). How Disney alters the actions of major and minor characters, and the construction of aging female characters and the key characteristics they exhibit during their fight for eternal youth, beauty, and social and political power will be analyzed, attempting to show how Disney is not a harmless substitute for a babysitter for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Disney animated movies in particular have been given much attention for its long history and popular production. Gender-role stereotyping of Disney's Princesses has been the subject of scrutiny of many scholars and analysts (e.g., Bálint, 2013;Dundes, 2001;Elnahla, 2015;Lacroix, 2004;Letaif, 2015;Maity, 2014;Seybold & Rondolina, 2018;Sun & Scharrer, 2004;Whitely, 2013). Bálint (2013), for instance, examined the portrayal of four of Disney's female characters between 1922 and 1948, from a feminist perspective.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Disney animated movies in particular have been given much attention for its long history and popular production. Gender-role stereotyping of Disney's Princesses has been the subject of scrutiny of many scholars and analysts (e.g., Bálint, 2013;Dundes, 2001;Elnahla, 2015;Lacroix, 2004;Letaif, 2015;Maity, 2014;Seybold & Rondolina, 2018;Sun & Scharrer, 2004;Whitely, 2013). Bálint (2013), for instance, examined the portrayal of four of Disney's female characters between 1922 and 1948, from a feminist perspective.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Stereotyping is also evident in representations of heroines and villainesses in Disney animated films. Elnahla (2015), for instance, investigated the intersection of age and gender in the characterization of the villainesses in six of Disney's popular animated films: Snow White and the Seven Dwarfs (1937), Cinderella (1950), Sleeping Beauty (1959), The Little Mermaid (1989), Tangled (2010), and Frozen (2013). She pointed out that heroines are depicted as young, attractive and noble whereas villainesses are rendered as old, unattractive, and semielite social misfits who constantly tried to obtain youth, beauty and/or power.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The film's phenomenal success at the time (earning $8 million on its initial release and winning a full-size Oscar statuette and seven miniature ones) heralded a golden age of animation and a rising influence of the Disney movies. By the mid-1970s, Disney studios started growing significantly (Elnahla, 2015). Today, Disney films have grown remarkably, exerting great influence in America and around the world.…”
Section: Ideologies In Walt Disney Animation Films: the Hidden And Mamentioning
confidence: 99%
“…Depictions of gender stereotypes in animated films (Coyne, Lindner, Rasmussen, Nelson, & Birkbeck, 2016;Seybold & Rondolino, 2018;Smith, Pieper, Granados, & Choueiti, 2010 ) and in television animated cartoons (e.g., Ahmed & Abdul Wahab, 2014;Coyne, Linder, Rasmussen, Nelson, & Collier, 2014;Leaper, Breed, Hoffman, & Perlman, 2002;Thompson & Zerbinos, 1995, 1997 have received considerable attention from researchers and analysts. Overrepresentation of male characters and depicting them as physically forceful leaders and superheroes (Baker & Raney, 2007) in contrast to the underrepresentation of female characters that frequently demonstrated passivity, affection and interest in physical appearance (e.g., Bazzini, Curtin, Joslin, Regan, & Martz, 2010;Elnahla, 2015;Fischer, 2010) were all negative messages of gender favoritism. Studies have shown that exposure to these gendered gender perceptions, preferences and social behaviors (G kçearslan, 2010;Holub, Tisak, & Mullins, 2008).…”
Section: Introductionmentioning
confidence: 99%